2011
DOI: 10.1152/ajpheart.00948.2010
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylate cyclase-α1is required for the cardioprotective effects of inhaled nitric oxide

Abstract: Reperfusion injury limits the benefits of revascularization in the treatment of myocardial infarction (MI). Breathing nitric oxide (NO) reduces cardiac ischemia-reperfusion injury in animal models; however, the signaling pathways by which inhaled NO confers cardioprotection remain uncertain. The objective of this study was to learn whether inhaled NO reduces cardiac ischemia-reperfusion injury by activating the cGMP-generating enzyme, soluble guanylate cyclase (sGC), and to investigate whether bone marrow (BM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…In myocardial injury, inhaled gaseous NO inhibited cardiomyocyte apoptosis and reduced infarct size [122-125]. The concentration of creatine kinase also decreased [122-124, 126, 127]. Increasing NO mediated respiratory complexes, leading to improved myocardial oxygen consumption and reduced production of superoxide.…”
Section: Nitric Oxide Corresponding Protection Strategymentioning
confidence: 99%
“…In myocardial injury, inhaled gaseous NO inhibited cardiomyocyte apoptosis and reduced infarct size [122-125]. The concentration of creatine kinase also decreased [122-124, 126, 127]. Increasing NO mediated respiratory complexes, leading to improved myocardial oxygen consumption and reduced production of superoxide.…”
Section: Nitric Oxide Corresponding Protection Strategymentioning
confidence: 99%
“…Hence, the modulation of NO/cGMP signaling is an important pharmacological target pathway for the prevention of cardiovascular diseases such as angina pectoris, hypertension, heart insufficiency, and atherosclerosis (7,57,62). The knowledge of the details regarding NO/cGMP signal transduction is essential for the understanding of the physiological and pathophysiological regulation and the modulation at diverse steps in this signaling pathway (Fig.…”
Section: Function Of No/cgmp/pkg Signaling Cascadementioning
confidence: 99%
“…We previously reported that neutrophils are required for inhaled NO to reduce MI size in wild-type (WT) mice subjected to transient left coronary artery occlusion [40]. Along these lines, we recently observed that NO breathing markedly decreased MI size in WT but not in sGCα1 -/-mice [50]. Furthermore, breathing NO decreased MI size in chimeric sGCα1…”
Section: Inhaled No Improves Outcomes After Cardiac Arrest and Cpr Inmentioning
confidence: 88%